Effect of strength training on endurance parameters and performance among under 19 provincial endurance athletes. - Bhavani, A.; Kuganesan, K. (Research Journal of Physical Education Sciences, 2017)
Purpose of the study was to examine the effect of strength training on endurance parameters and performance among under 19 provincial endurance athletes. To achieve this, the present study ninety(N=90) endurance athletes from 5000M events in Northern Province in Sri Lanka has been assigned. Thirty (n=30) subjects have been selected from each event (800M, n=30), (1500M, n=30), (5000M, the effect of training packages on body mass index (BMI), VO endurance performance. Pre test and post test data were collected from selected variables before the intervention and after intervention. T test was administered to find out significant difference between pre test and post test. Further one way analysis of variances (ANOVA) was done to find out significant differences of variables among the above three events athletes. Result revealed that strength training did not show significant differences on the intervention of VO Moreover F ratio did not show significant differences on BMI (post intervention) and ME events athletes. Finding revealed that strength training has improved MS, ME, BMI and endurance performance of 800M and 1500M athletes. However Strength training did not improve endurance performance of 5000M athletes.
Keywords: BMI; VO2max; Muscular Strength; Muscular Endurance; Performance